1990
DOI: 10.1136/gut.31.7.786
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen metabolites in experimental colitis.

Abstract: Reactive oxygen metabolites are potent inflammatory mediators that may be involved in tissue injury in inflammatory bowel disease. To evaluate their role in inflammatory bowel disease, we investigated the effects oflowering the activities of reactive oxygen metabolites in experimental colitis induced by intracolonic administration of acetic acid in rats. Intracolonic administration of5% acetic acid caused severe inflammation (mean (SEM) inflammatory score was 24*3 (0.7) of a maximum score of 32). Acetic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(106 citation statements)
references
References 19 publications
5
100
0
1
Order By: Relevance
“…Increased ROS levels in the intestinal epithelial cell membrane may lead to oxidative damage mediated by free radical attacks and lipid peroxidation, which may be an early critical event in the model of experimental IBD. Acute attacks of UC lead to an inflamed colonic mucosa, which contributes to an excess production of reactive oxygen metabolites by lipid peroxidation (18). Inflammatory tissue injury may further stimulate ROS production and reactive oxygen metabolites, thus forming a positive feedback loop and rendering the antioxidant system insufficient (19).…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS levels in the intestinal epithelial cell membrane may lead to oxidative damage mediated by free radical attacks and lipid peroxidation, which may be an early critical event in the model of experimental IBD. Acute attacks of UC lead to an inflamed colonic mucosa, which contributes to an excess production of reactive oxygen metabolites by lipid peroxidation (18). Inflammatory tissue injury may further stimulate ROS production and reactive oxygen metabolites, thus forming a positive feedback loop and rendering the antioxidant system insufficient (19).…”
Section: Discussionmentioning
confidence: 99%
“…A balance is maintained between oxidant and antioxidant systems under physiological conditions, but it is impaired in pathological success. Oxidant-mediated injury plays an important role in the pathophysiology of IBD [64] . It has been suggested that intestinal damage in IBD is related to increased free radical production and to impaired antioxidant defence systems [65] .…”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…Oxidation stress in the large intestine is a cause and an aggravation factor not only of ulcerative colitis and Crohn disease but also of ischemic enteritis, infectious enteritis, and radiation colitis [22][23][24][25][26]. In the local inflammatory area of the large intestine, inflammatory infiltrative cells such as neutrophils produce various reactive oxygen species, which may damage the large intestinal mucosa.…”
Section: Large Intestinal Inflammation and Hspmentioning
confidence: 99%